A STUDY OF PROPERTIES OF THE RECURRENT MULTI-STEP MODELS FOR INTERANNUAL DYNAMICS OF DIATOM ALGAE COMMUNITIES IN EPIPHYTON - V. A. Parensky; E. V. Levchenko (Известия ТИНРО)
Epiphytic diatoms develop seasonally. On macrophytes they reach the highest density in the middle of summer and have the minimum density in winter. This pattern gives an opportunity to apply a tool of difference (recurrent) equations for testing the concept of density regulation in interannual dynamics of their number. Detailed scheme of the model is developed; the model is applied for the diatoms dynamics in macroalgae epiphyton of Ulva lactuca Linnaeus in three areas of Peter the Great Bay, Japan Sea (Amur Bay, Ussuri Bay, and Stark Strait). The model parameters are evaluated by means of SYSTAT 5 and STATISTICA 8 software. The model results do not contradict the data of observations. Its determination (R2 ) exceeds 0.62 in all cases. Selected coefficients of the model have rather small relative errors (< 11 %) which never change the sign of the coefficients. Generally, the modelled dynamics of relative number of epiphytic diatom communities is complicated, pseudochaotic. It differs between the areas. Reproductive capacity of the epiphytic diatom community is the lowest in the Stark Strait and the highest in the Amur Bay. In both these areas, alternation patterns are modelled as periods of chaotic dynamics and the periods with a limit cyclicity. Resistance of the epiphytic diatom communities to variations of the main limiting factors of the environments decreases in the order: Amur Bay — Stark Strait — Ussuri Bay.